Frass and Furious: Unfolding the Potential of Insect Frass as Soil Fertilizer - Christos G. Athanassiou; Christos I. Rumbos (Agrochemicals)
Over the past decade, insect farming has garnered significant scientific and commercial attention due to its potential as a sustainable and efficient alternative nutrient source for both animal feed [...]